Chapter L'uso dell'Unità Didattica Digitale per lo sviluppo della competenza lessicale - La Grassa, Matteo (Strumenti per la didattica e la ricerca, 2021)
This paper presents the main features of the UDD (Unità Didattica Digitale), a new operational model developed specifically for language teaching in e-learning. In particular, we will focus on how this model can be used to develop lexical competence, the features of which will be briefly defined, mainly by referring to the different phases envisaged in the teaching plan. The paper will then illustrate the possibilities that the UDD model offers for activating and supporting the development of lexical competence, the types of activities that can be carried out and in which ways the model can be used, highlighting the positive aspects and the critical issues still to be resolved.